(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Metals can be bio-accumulated and bio-magnified via the food chain and finally assimilated by human consumers resulting in health risk. Three species of imported marine frozen fishes namely; Sardinella aurita, Clupea harengus and Scomber scombrus were investigated for metallic elements using AA240FS Fast Sequential Atomic Absorption Spectrometer. Nine elements belonging to the groups of light metals (calcium and magnesium), biological essential heavy metals (copper, chromium, manganese, iron and nickel) and non-essential heavy metals (lead and cadmium) were evaluated. Calcium was the highest (290.75 ppm) concentrated light metal, Fe was the highest (2.587 ppm) concentrated biological essential heavy metal, while Pb and Cd were the highest (0.053 ppm) concentrated non-essential heavy metals. Sardinella aurita had significantly (P < 0.05) highest concentration of Cu (0.05) and Fe (2.59), while S. scombrus had the highest concentration of Mn (2.18 ppm). The concentrations of all biological essential heavy metals were below their Recommended Daily Allowance (RDA). Scomber scombrus had the highest concentration of Cd with mean values higher than the Tolerable Upper Intake Limit of 0.02mg/day. Therefore screening on importation of frozen fish, for non-essential heavy metals is recommended